Novel Approaches and Future Directions for Pesticide Ecological Risk Assessment to In-Soil Fauna - Carniel, Leticia Scopel Camargo (2019)
The aim of the present work was to improve the ecological risk assessment (ERA) of plant protection products (PPPs) to in-soil fauna in European Union based on the new Scientific Opinion of European Food Safety Authority (EFSA) (2017) and to execute the same approach in Brazilian scenarios. The tiered approach, which modes from more protective to higher complexity tests was used. Bravonil 500® (500 g.L-1 chlorothalonil) and Lorsban 480® (480 g.L-1 chlorpyrifos) were used as model PPPs. In the lower tier, reproduction laboratory tests with eleven in-soil organisms (five collembolans and six oligochaete species) were performed using ISO and OECD standard protocols with adaptations when necessary. Effect concentrations to 10% (EC10) and 50% (EC50) of the tested species were estimated and has been used on the first intermediate tier to elaborate the species sensitivity distribution (SSD) curves. These allowed to estimate the hazard concentrations (HC) assumed to protect 95% (HC5) or 50% (HC50) of the Collembola and Oligochaeta species. In a second intermediate tier, microarthropod community tests in Mediterranean soil using native organisms under laboratory conditions were performed. Besides of toxicity data, exposure was also estimated though PPPs predicted environmental concentrations (PECs) in soils considering European and Brazilian scenarios. Toxicity-exposure ratios (TER) were determined and compared with the trigger values to estimate the potential risk for these organisms. Finally, mesocosms tests in terrestrial model ecosystem (TME) using subtropical soil from Brazil were executed as a surrogate higher tier. For these experiments two different application scenarios were considered: 1) continued application (2x) based on the general agricultural procedures for soybean crop application; 2) single application, estimated based on Europe’s ERA instructions for higher tier testing. Lower tier chlorothalonil results to collembolans indicates the higher EC10 to the standard Folsomia candida (2.44 mg a.i. kg-1). However, there were overlaps on confidence interval to all tested species, indicating similar sensitivity to this fungicide. Among oligochaetes EC10 data, Eisenia andrei did not present a protective value for all tested species (22.69 mg a.i. kg-1). Chlorpyrifos was highly toxic to all collembolans tested (EC10 < 0.004 mg a.i. kg-1). Among oligochaetes, E. andrei was the least sensitive species in EC10 data (5.2 mg a.i. kg-1). The non-protectiveness of E. andrei when estimating risk to all oligochaetes species is clear in the SSDs approach (chlorothalonil: HC5: 2.98 and chlorpyrifos: HC5: 0.084 mg a.i.kg-1). The lower tier must be the most protective step in ERA, which was not observed to oligochaetes in the present work. Microarthropod community tests pointed to similar results to those found in the SSDs approach for collembolans (chlorothalonil: EC20: 1.90 – 9.36 and chlorpyrifos: EC20: 0.0020 - 0.024 mg a.i. kg-1), corroborating risk prediction in laboratory tests to Collembola species. Results indicates that the used approach to test for microarthropod communities could be useful as an intermediate tier. However, standardization is still necessary, due the high variability in dataset, mainly due to mites. Higher tier though TMEs tests showed a population reduction of microarthropods due to both products, even at the lowest concentrations tested, regardless the exposure scenario. Results also indicated an absence of recovery eight weeks after application (Bray-Curtis dissimilarity > 35%). Effects on earthworms in TMEs were not observed due the low number of organisms. No effects has been observed in enchytraeids either. The previous tiers were capable of predicting risks, which were still detected at higher tier, mostly for collembolans. EFSA (2017) suggestions to estimate PPPs risks to in-soil fauna are suitable on ERA and the proposed approaches for intermediate tiers could help risk assessors and management. At Brazil, it is suggested to change the current regulation shifting from acute testing towards the adoption of chronic reproduction tests and the addition of more species than just E. andrei. Not only the acute test have been highlighted as inefficient in predicting risks, this earthworm species was not the most sensitive species to both products in lower and intermediate tiers with SSDs. Furthermore, research in dissipation time (DT) of PPPs in Brazilian soils are immediately necessary to estimate accurate PEC values under different scenarios to better predict PPPs risks.